Introduction to the numerical solution of Markov chains - Stewart, William J., 1946- (Princeton University Press, 1994)
Markov Chains -- Direct Methods -- Iterative Methods -- Projection Methods -- Block Hessenberg Matrices -- Decompositional Methods -- LI-Cyclic Markov -- Chains -- Transient Solutions -- Stochastic Automata Networks -- Software.